Outcomes and incidence of PF-ILD according to different definitions in a real-world setting - Torrisi, Sebastiano Emanuele; Kahn, Nicolas; Wälscher, Julia; Polke, Markus; Lee, Joyce S.; Molyneaux, Philip L.; Sambataro, Francesca Maria; Heußel, Claus Peter; Vancheri, Carlo; Kreuter, Michael (Frontiers in pharmacology, 2021)
Background: Almost one-third of fibrosing ILD (fILDs) have a clinical disease behavior similar to IPF, demonstrating a progressive phenotype (PF-ILD). However, there are no globally accepted criteria on the definition of a progressive phenotype in non-IPF fILD yet. Four different definitions have been used; however, no internationally accepted definition currently exists.Research Question: To compare the clinical and functional characteristics of progressive fILD according to the currently available definitions.Study design and methods: Cases of fILD were identified retrospectively from the database of the tertiary referral center for ILD in Heidelberg. Lung function, clinical signs of progression, and radiological changes were evaluated. Patients with fILD were considered to have progression according to each of the four available definitions: Cottin (CO), RELIEF (RE), INBUILD (IN), and UILD study. Lung function changes, expressed as mean absolute decline of FVC%, were reported every 3 months following diagnosis and analyzed in the context of each definition. Survival was also analyzed.Results: A total of 566 patients with non-IPF fILD were included in the analysis. Applying CO-, RE-, IN-, and UILD-definitions, 232 (41%), 183 (32%), 274 (48%), and 174 (31%) patients were defined as PF-ILD, respectively. RE- and UILD-criteria were the most stringent, with only 32 and 31% patients defined as progressive, while IN- was the most broad, with almost 50% of patients defined as progressive. CO- definition was in-between, classifying 41% as progressive. PF ILD patients with a UILD definition had worse prognosis.Interpretation: Depending on the definition used, the existing criteria identify different groups of patients with progressive fILD, and this may have important prognostic and therapeutic implications.
Gesehen am 25.02.2022